Transparansi dan Akuntabiltas Pengelolaan Alokasi Dana Desa dengan Budaya Tunjuk Ajar Melayu di Desa Bukit Batu Kecamatan Bukit Batu Bengkalis - Desi Rusfiani; Ria Nelly Sari; Yesi Mutia Basri (Politeknik Negeri Bengkalis, 2022)
Village Funds provided by the Central Government are a form of state attention to advancing the economy In rural areas. In managing village funds, it is demanded that there be an aspect of good governance wherein the management of village funds at each stage, namely planning, implementation, administration, reporting and accountability needs to be implemented in transparency and accountability.This study aims to analyze qualitative data using ethnographic methods through the role of Tunjuk Ajar Melayu culture in increasing transparency and accountability in the management of village fund allocations in Bukit Batu Village, Bukit Batu District, Bengkalis Regency with eight (8) informants, namely the village head, village treasurer , village secretaries, village head, chairman of the Bukit Batu village BPD as the main informant who understands village fund allocations as well as village community leaders, village religious leaders, and LAM figures who understand the Malay Demonstration Culture in Bukit Batu village. Data collection was carried out through observation and interviews.The results of the study show that Village Fund Management is up to standard and applies the principles of Transparency and Accountability. The form of Transparency is through the installation of billboards and activity information boards as well as Accountability as outlined in the form of accountability for budget use. Cultural values have been applied by village officials to avoid fraudulent behavior in managing Allocations Village Fund. With the Malay Teaching and Learning Culture which contains Islamic and customary values based on sharak and the book of Allah which is in the identity of the Malay people, this is a guide for the village community in Bukit Batu in carrying out all actions and activities including in the implementation of transparency and accountability in the management of ADD.Transparency and accountability related to honesty and responsibility, this is the same as what is contained in the Malay Teaching and Learning culture which contains the values of shidiq' (honesty), Amanah' (trustworthiness), tabligh (smart and energetic in acting) and fathonah in being accountable for an action.Keywords: Transparency , Accountability, Culture, Malay Â Teaching and Learning, Village Fund Allocation Management